РЕЗИСТЕНТНІСТЬ ГАМАРИД PONTOGAMMARUS ROBUSTOIDES (SARS) (CRUSTACEA: AMPHIPODA) ДО ЗМІН ТЕМПЕРАТУРИ ВОДНОГО СЕРЕДОВИЩА - Романенко, В. Д.; Крот, Ю. Г.; Леконцева, Т. І.; Фриновська, Т. В.; Подругіна, А. Б. (Marine Ecological Journal, 2023)
Thermal resistance of gammarids Pontogammarus robustoides (Sars, 1894) under static and dynamic effects of raised temperatures on aquatic natural type (operating temperature range of 4 – 32°C) and laboratory (adapted to the narrow range of temperatures 19 – 25°C) populations were investigated. The level of heat resistance of individuals on the degree of variability of the temperature conditions of the environment was shown. In static exposure to high temperatures for representatives from both laboratory and natural populations vital temperature was 32°C, absolutely lethal – 35°C (24 h exposure). In static conditions, the action of extreme temperatures (38 °C) and progressive growth of temperature of the aquatic medium 6 and 12°C/hr lethal time (Lt50) and average value of the critical thermal maximum (CTMax) for individuals of laboratory population of P. robustoides (respectively 18.3 min and 37.5–39.6°C) were significantly lower than indicators of natural population (respectively 29.8 min and 38.3–39.7°C). Interpopulational and age features of behavioral responses and individual variability of the thermal stability of individuals were identified. The optimization of culture conditions of P. robustoides in control systems were discussed.